ANALISIS PERAN GURU DALAM MENINGKATKAN MINAT BACA SISWA SEKOLAH DASAR MELALUI METODE PEMBELAJARAN INOVATIF - Nadirah Dira; Miranda Agrimel (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
This study aims to analyze the role of teachers in improving elementary school students’ reading interest through innovative learning methods. The low level of students’ reading interest has become one of the problems affecting the learning process and outcomes, therefore effective efforts are needed to foster a literacy culture from an early age. This research used a qualitative method with a descriptive approach, while the data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed that teachers play important roles as facilitators, motivators, guides, and innovators in improving students’ reading interest through the application of various innovative learning methods, such as the use of interactive learning media, shared reading activities, storytelling, educational games, group discussions, and project-based learning. The implementation of these methods was able to create a more interesting, active, and enjoyable learning atmosphere so that students became more enthusiastic, motivated, and accustomed to reading activities. In addition, support from the school environment, the availability of literacy facilities, and teachers’ creativity in managing learning also became supporting factors in increasing students’ reading interest. Based on the results of the study, it can be concluded that the application of innovative learning methods by teachers has a positive influence on improving elementary school students’ reading interest and can help create a better literacy culture in the school environment.